2020
DOI: 10.1002/cncy.22273
|View full text |Cite
|
Sign up to set email alerts
|

Detection and comparison of EGFR mutations from supernatants that contain cell‐free DNA and cell pellets from FNA non–small cell lung cancer specimens

Abstract: BackgroundEpidermal growth factor receptor (EGFR) is an important marker for targeted therapy in patients with advanced non–small cell lung cancer (NSCLC). The samples obtained with minimally invasive biopsy techniques are usually small, and this limits their application in tissue subtyping or molecular profiling. The supernatants obtained after centrifugation of fine‐needle aspiration (FNA) samples are typically discarded. However, these fractions might contain cell‐free DNA that could be tested for EGFR muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The supernatant from this process is typically discarded, but recent studies have suggested that supernatant fluid from cell block formation is a potential alternative source of DNA for biomarker testing. [11][12][13][14][15][16][17][18][19] Multiple studies have shown very good concordance rates between supernatant (either from body fluids or FNA specimens) and FFPE cell blocks for detecting mutations, and some studies have shown an improved mutation detection rate with DNA from supernatant as compared with cell blocks. 11,15,19 In addition, in cases where neither cell blocks nor aspirate smears were prepared (eg, bile duct brushings with only ThinPrep slides), molecular studies performed on the supernatant has been shown to have a higher sensitivity than cytology alone.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant from this process is typically discarded, but recent studies have suggested that supernatant fluid from cell block formation is a potential alternative source of DNA for biomarker testing. [11][12][13][14][15][16][17][18][19] Multiple studies have shown very good concordance rates between supernatant (either from body fluids or FNA specimens) and FFPE cell blocks for detecting mutations, and some studies have shown an improved mutation detection rate with DNA from supernatant as compared with cell blocks. 11,15,19 In addition, in cases where neither cell blocks nor aspirate smears were prepared (eg, bile duct brushings with only ThinPrep slides), molecular studies performed on the supernatant has been shown to have a higher sensitivity than cytology alone.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation status of 10 driver genes in matched tumor samples was detected by a NGS panel (Amoy Diagnostics), 17,18 which can detect hotspot mutations/fusions in genes of EGFR, KRAS, BRAF, NRAS, HER2, PIK3CA, ALK, ROS1, RET, and MET in one single test. The detection process described by the manufacturer was followed.…”
Section: Mutation Status Analysis Of Driver Genes In Matched Tumor Sa...mentioning
confidence: 99%
“…Traditional or liquid-based preparations are suitable for the application of exome sequencing or customized panels and, especially, May Grunwald Giemsa (MMG)-stained slides can be easily microdissected to obtain enriched samples. Supernatants may provide adequate material for the detection of driver mutations in oncogene-addicted cancers, helping to avoid the sacrifice of diagnostic stained smears (14). Especially during the natural history of longlasting cancers, the possible contribution of core-needles as repeat biopsies is debated.…”
Section: Biological Techniquesmentioning
confidence: 99%